Penerapan Media Interaktif Articulate Storyline dalam Pembelajaran Ikatan Kimia di SMA - Cita Sundari; Pasar Maulim Silitonga (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to find out whether the learning outcomes of students who are taught with the application of interactive media articulate storyline are higher than the learning outcomes of students who are taught with the application of PowerPoint media. This research was carried out in the odd semester of TA 2021/2022 in November 2021 at Al-hikmah Medan Private High School. The population in this study was the entire high school X MIPA grade consisting of 2 classes namely X MIPA 1 and X MIPA 2. The sample of the class in this study was a saturated sample and the sample of student was purposively taken about 25 students of each class who are relatively homogeneous in status. The research design used constitutes the pretest-posttest control group design. The instruments used are multiple choice shaped test instruments related chemical bonding material. Hypothesis testing is performed by using the right-part t-test one sample group and two sample group. The research results showed that the average student learning outcomes taught with Articulate Storyline interactive media were higher than the minimal stickness criterion. Furthermore, it was obtained that student learning outcomes taught with articulate storyline interactive media were higher than student learning outcomes taught with powerpoint media. In classes taught with interactive media articukate storyline a presentation of student who achieved a minimum sticknes criterion of 92%.